Methodology for organization of protection measures against technical means of competitive in-telligence - Заболотний, В.І.; Єрмолович, А.В. (Radiotekhnika, 2017)
Protection is achieved by introduction of competitive intelligence complex systems of protection. Development of protective measures is in accordance with a defined scope of work. It was determined that the development of control measures protection measures aimed at preventing failure and inability to measures designed to protect the developed object. The main goal of the research is to determine the consistency in defending the basic concepts of competitive intelligence, separation and setting targets for all the major steps to develop measures to protect against competitive intelligence, develop methods of organizing data work.